Lung Adenocarcinoma With Extensive Vascular Invasion and Retinal Metastasis: A Case Report - Bassem Alhariri; Arwa Elfatih; Osman Osama Elhassan; Mohamed Elfatih; Aya Mohamed Kheir; Razan Elkhatib (Respirology Case Reports)
ABSTRACT A 34‐year‐old Ghanaian male with no past medical history presented to our hospital with dyspnoea, left‐sided chest pain, and left‐eye visual disturbance. Imaging revealed a large mediastinal mass with vascular invasion, left pleural and skeletal metastases. A lung biopsy confirmed lung adenocarcinoma (LUAD) with mixed solid and lepidic growth patterns, showing 80% PD‐L1 expression. Positron emission tomography (PET) identified a highly active lesion in the left eye, suggestive of retinal metastasis. Ophthalmologic evaluation confirmed retinal involvement. Given ROS1 positivity, Crizotinib was initially prescribed but switched to Lorlatinib due to concerns regarding retinal involvement. The patient demonstrated rapid clinical improvement, including notable visual recovery, with stable performance status after 1 month. This case underscores LUAD's potential for atypical metastasis, such as to the retina, necessitating comprehensive assessment and personalised management strategies. The shift from Crizotinib to Lorlatinib highlights the importance of targeted therapy in managing advanced NSCLC with rare metastatic involvement.